The effects of public and private health spending on under-five mortality: Do female literacy and good governance matter? - Alnahdi, Saleh (Edelweiss Applied Science and Technology, 2025)
This paper sought to investigate the effects of total, public, and private health expenditure on under-five mortality rates (U5MRs). The study is carried out using simultaneous equation models in a sample of 73 Asian and African countries spanning the period 1995-2023. Findings showed that total and public health expenditures are likely to reduce under-five mortality rates in both African and Asian regions. Whereas private health spending was found to be insignificantly related to child deaths in most cases of estimation. Estimation demonstrate also that female literacy and the quality of institutions play a significant role in mediating the relationship between health spending and U5MRs. Moreover, the study also showed that improvements in water sanitation, physicians’ density, and GDP growth all work together to decrease the plausibility of U5MRs. From a policy standpoint, the study calls for health policymakers in African and Asian regions to increase the proportion of their annual budgets to healthcare as a strategy to reduce U5MRs.